The Spirit World & North American Indian Mortuary Practices - Grace Keyes (Revista Espaço Acadêmico, 2021)
From earliest times, North American Indians[i] have shared some significant commonalities. Salient among these is a deep spiritual connection to the natural world. There is among most Native American Indian tribes and nations a strong animistic tradition that embraces the existence of a spirit world and the interconnection between humans and this spirit world. Indeed, this can be found in most indigenous populations of the entire hemisphere. The belief in spirits is generally reflected in many aspects of Indian life including mortuary customs. It should be noted that the historical and political processes of acculturation and assimilation have had a tremendous impact on Native American Indians in the United States. Even though some elements of the past persist, mortuary practices have been altered considerably, and continue to change, as a result of these acculturative processes. This paper focuses on a few traditional mortuary practices that illustrate how Native American animistic beliefs affected such customs.